Intermittent Irrigation for Improving Rhizobacteri Population Dynamics and Rooting of Local Rice Varieties - Bambang Isnawan; Agung Astuti; Zulfa Abida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Intermittent irrigation is one of the rice cultivation technologies developed in Indonesia and the world. This study aims to determine the interaction between superior rice varieties with a watering system and rhizobacteria population dynamics, root development, and rice yield. This research was conducted for four months. The study used experimental methods on land compiled with a Factorial 3x4 Strip-Plot experiment design with a Completely Randomized Block Design (RCBD). Factor I is a watering system consisting of 3 treatments i.e. conventional irrigation, intermittent irrigation ten days of dry 5-day watering, and intermittent irrigation seven days of dry 3-day watering. Factor II is rice varieties consisting of 4 i.e. Cempo Merah, Inpari 23, Sintanur, and Inpari 42. The results showed no interaction between the irrigation system and rice varieties to rhizobacteria populations, rooting, and rice yields. The 7-day drying watering system has a relatively larger population of Rhizobacteria in week 16 and increases the length of the roots than other watering treatments. Intermittent irrigation provides grain weight per clump, which is no different from conventional irrigation. Inpari 23 rice varieties have a population of Rhizobacteria week 16 more and weigh 1000 seeds higher than the varieties Inpari 42. The yield of superior rice varieties Inpari 23, Sintanur, and Inpari 42 is higher than Local Cempo Merah rice varieties. Inpari 23, Sintanur, and Inpari 42 varieties can be cultivated by intermittent irrigation.